Functional Materials: Processing, Utilisation, Protection - V. Korablev, Vadim (Trans Tech Publications Ltd, 2023)
This book collects articles based on the results of scientific and engineering research in applied materials science and technologies of materials treatment. The first two parts include research on metal surface treatment technologies to improve their functional characteristics and specific features of friction welding technologies in modern machine building. The corrosion behaviour of structural materials and corrosion protection methods with bio inhibitors and protective coatings are analysed in the next two parts of the book. Here is also presented the research on the hydrogen compatibility of structural materials that is today the actual issue in the area of the energy transition. Properties of functional ceramics, glasses and perspective materials for micro- and optoelectronics are investigated and analysed in the fifth and sixth chapters. The last part of the book is devoted to researching the application of cement replacement materials - a modern trend in the spirit of sustainability in the construction industry. This special edition will be helpful to specialists in machinery, micro- and optoelectronics and construction.